Prática pedagógica reflexiva em cursos de formação continuada : um estudo crítico etnográfico - Correa, Maria Antonia (2013)
This study aims to investigate the experiences of teachers about reflexive pedagogic practice, in continuing education courses, in ‘Meninos do Futuro’ State School, located in the Social Educational Centre in the Pomeri Complex, in the Planalto district, Cuiabá/MT. The specific aims of this research are: (1) To get to know about the teachers’ reflections on their pedagogical practice; (2) To verify if the reflections made by the teachers are consonant with critical-reflexive theories; (3) To understand how continuing education courses contribute to the teachers’ reflections and changes of attitudes. Among the assumptions that guided this study are: (1) Teacher empowerment, through continuing education courses, creating potential for inclusion, since teacher’s critical thinking can (and should) result in the fostering of the development of student’s critical thinking; (2) Themes of interest to the teacher, discussed in the continuing education courses, provide opportunity for positive reflections about the pedagogical practice in the classroom; (3) Knowledge of critical and reflexive theories contributes to changes of mindset and attitudes towards reality. This is a qualitative, collaborative ethnographic research. The data were collected through participant observation in order to understand the school content, including notes in a field diary and audio recorded interviews. The study is based on the theory about the critical reflexive training, where the continuing education program is the idea of a process involving critical reflection about the pedagogical practice (GIROUX. 1992; CONTRERAS, 2002; BARROS, 2010). This study involved teachers from the school in continuing education courses, within a multiplying vision, mediating reflexive and collective work. The data analysis was based on the approach of content analysis (BAUER e GASKELL, 2004; BARDIN, 2009; RICHARDSON, 2011) in three chronological phases: the pre-analysis, exploration of the material and the treatment of the results, inference and interpretation. The analysis showed that the teachers of the ‘Meninos do Futuro’ school weave reflections about their pedagogical practice, based on reflection-on-the action’ and reflection-in-the action’. The reflections made by teachers, through continuing education, provided a more critical view of their pedagogical practice, seeking the inclusion of the students from ‘Meninos do Futuro’ school.